Translating Justice and Therapy: The Drug Treatment Court Networks - Moore, Dawn (The British journal of criminology, 2007)
Drawing on research from Canada's two operating drug treatment courts, this paper explores the relationship between therapy and law, revealing a network in which expert knowledges are freed from expert actors. This uncoupling allows for the translation of the goals and interests of legal and therapeutic actors involved in the court. This uncoupling affects the ways in which both justice and therapy are imagined and articulated in these settings. While the bid to cure the criminal addict is often assumed to be a benevolent and progressive alternative to incarceration, the analysis reveals that therapeutic enterprise has decidedly punitive effects, amplifying control and erasing protections in the name of curing the offender